Upper bound of degrees of freedom in cognitive MIMO interference network with user cooperation - Shi-lei ZHU; Na-e ZHENG; Sheng WANG; Han-ying HU (Tongxin xuebao)
In(K+1)-user cognitive MIMO interference network,conventional algorithms distinguish the interference of primary users and secondary users by aligning them to the different interference space,separately.Therefore,it leads to the loss of spatial degrees of freedom(DoF).From the perspective of multiplexing the interference space,a new upper bound of DoF and its necessary condition was deduced.Furthermore,to verify the rationality and validity of the new upper bound,a cooperative joint interference alignment algorithm,in which a joint interference alignment indicator was designed and proposed based on norm theory and Rayleigh-Ritz theorem.The effectiveness of the algorithm was analyzed.Theoretical analysis and simulation results show that the new upper bound of DoF breaks upper bound given in the existing papers,and it can be achieved by the proposed algorithm.